Management of an orthognathic surgery treatment in a skeletal class III patient: case report. - Orozco Jiménez, Daniela; Andrade Torres, Alejandro; Castro García, Alejandra; Roca Pereda, Raul; Casillas Santana, Miguel Angel (Revista Estomatología, 2021)
Introduction: The treatment established as the gold standard for skeletal deformities of the craniofacial complex is orthodontic treatment combined with orthognathic surgery, to achieve occlusal stability, facial harmony, improved mastication, phonation and breathing. The conventional orthognathic surgery protocol consists of 3 phases: pre-surgical orthodontic treatment, orthognathic surgery and post-surgical orthodontics. Case Report: 18 year old female patient with skeletal class III. She presents occasional pain, crepitation and luxation of the temporomandibular joint, laterognathia. Treatment: Conventional orthognathic surgery of both jaws with unilateral sagittal osteotomy. Results: The objectives of the treatment plan were achieved 1 year and 9 months after starting orthodontic treatment. Conclusion: With a good diagnosis and treatment planning orthodontic - maxillofacial surgery ensures excellent results, as well as bone stability and occlusal harmony post-surgery.